Digital Innovation in Smart Waste Sorting Using Renewable Energy for Sustainable Startups - Untung Rahardja; Nuke Puji Lestari Santoso; Fitra Putri Oganda; Muchlishina Madani; Muhamad Stabil Tanwin Saputra (Pandawan Sejahtera Indonesia, 2026)
The accumulation of inorganic waste in urban environments requires inno- vative technological solutions that support the Sustainable Development Goals (SDGs), particularly SDG 11 (Sustainable Cities and Communities) and SDG 12 (Responsible Consumption and Production). Smart waste management systems integrating Artificial Intelligence (AI) and the Internet of Things (IoT) have emerged as promising digital innovations to improve waste sorting efficiency. This study presents the development of a smart waste sorting system called Orange Box, designed to support sustainable startup initiatives in environmental technology. A major challenge in deploying IoT-based devices in outdoor public areas is the limited availability of conventional electrical infrastructure, where reliance on extension cables is inefficient and potentially unsafe. Therefore, this research aims to design and evaluate an independent off-grid electrical system based on renewable energy to ensure continuous operation of the device. The proposed system utilizes solar panels as the primary energy source, with energy conversion and distribution managed through a 500W inverter and a 20A Power Supply Unit (PSU) that supplies power to a Raspberry Pi 5–based control system. Experimental measurements indicate that the system operates with an average power consumption of approximately 10–12W and reaches a peak load of 17.17W during active waste sorting operations. The estimated daily energy consumption ranges from 288Wh to 338Wh when considering inverter efficiency. These findings demonstrate that integrating renewable energy infrastructure with IoT-based smart waste sorting technology represents a viable digital innovation to support sustainable startups while contributing to SDG 7 (Affordable and Clean Energy).